Collective Rights and Democratic States: A New Framework for Addressing Global Socio-economic Inequality - Radaković, A (Informa UK Limited, 2019)
This article will present the argument for treating democratic states as moral and not only legal collective entities; that is, it will apply the theory of collective rights of cultural groups in a (closed) domestic political setting to democratic states in international relations. Numerous experiences by self-identifying cultural groups bear witness to the fact that morally important objectives are not always reached by merely treating individuals as the sole bearers of moral status. In order to prevent latent cultural imperialism, many countries around the world have adopted various models of collective rights protection and policies of preferential treatment for these groups. This article will examine whether it is possible to make a parallel between cultural groups and democratic states; in particular, whether it is feasible to think of democratic states as moral entities and what the normative implications of such a view for contemporary international relations and trade would be.
Keywords: Democratic states; Cultural groups; Collective rights; International relations